Rheumatoid arthritis and cardiovascular disease in relation to cytomegalovirus infection: a pilot cross-sectional study - Mohammed Ahmed Al-Kaif; Laith A. I. K. Al-Kaif; Zaid Saad Madhi; Dalya Talal Fathi Al-Azzawi; Wael Rasheed Obaead Alfatlawi; Sarah Kassab Shandaway Al-Zamali; Fatin Alaa Abdul Ameer Mahdi; Haibo Liu (Frontiers in Medicine, 2026)
Background Patients with rheumatoid arthritis (RA) face increased cardiovascular disease (CVD) risk not fully explained by traditional factors. Chronic cytomegalovirus (CMV) infection may contribute through immune activation and vascular inflammation. This pilot study investigated associations between CMV serostatus, vascular endothelial growth factor A (VEGF-A), and inflammatory markers in patients with RA and/or CVD. Methods This cross-sectional study enrolled 76 participants (CVD = 40, RA = 18, RA+CVD = 18). Serum anti-CMV antibodies, VEGF-A, and IL-6 were measured by ELISA; CRP was assessed by agglutination; and CMV viral load was quantified by RT-PCR. Group comparisons analyses were performed. Results CMV seroprevalence was 80.3% overall (CVD: 82.5%; RA: 77.8%; RA+CVD: 77.8%). VEGF-A levels were higher in CMV positive vs. CMV negative individuals, but the differences were not statistically significant; these data are inconclusive regarding a true association (e.g., overall mean: 67.8 vs. 44.5 pg/mL, p = 0.12). No significant differences were found among clinical groups for CMV IgG positivity, viral load, IL-6, CRP, or VEGF-A ( p > 0.05 for all). However, viral load, IL 6 and CRP showed numerical increases that did not reach statistical significance. Conclusions This pilot study is underpowered for definitive conclusions and should be interpreted as exploratory and hypothesis-generating. Although VEGF-A levels were higher in CMV positive individuals, the association was not statistically significant and the data are inconclusive. Larger, adequately powered studies are needed to clarify the role of CMV and angiogenic pathways in RA associated CVD.